2022
DOI: 10.3390/ijms231810268
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis Burdens in Diabetes Mellitus: Assessment by PET Imaging

Abstract: Arteriosclerosis and its sequelae are the most common cause of death in diabetic patients and one of the reasons why diabetes has entered the top 10 causes of death worldwide, fatalities having doubled since 2000. The literature in the field claims almost unanimously that arteriosclerosis is more frequent or develops more rapidly in diabetic than non-diabetic subjects, and that the disease is caused by arterial inflammation, the control of which should therefore be the goal of therapeutic efforts. These views … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Moreover, there is an inability to define emia, hypoxia, and subsequently leading to diabetic foot [24,25]. Hyperlipidemia can further reduce blood flow to the feet by exacerbating vascular atherosclerosis, thereby worsening the condition of diabetic foot [26,27]. However, the author found that fasting blood glucose and blood cell analysis were not risk factors for diabetic foot, which may be associated with their higher variability and differ from the conclusions of other studies, possibly due to the sample size.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, there is an inability to define emia, hypoxia, and subsequently leading to diabetic foot [24,25]. Hyperlipidemia can further reduce blood flow to the feet by exacerbating vascular atherosclerosis, thereby worsening the condition of diabetic foot [26,27]. However, the author found that fasting blood glucose and blood cell analysis were not risk factors for diabetic foot, which may be associated with their higher variability and differ from the conclusions of other studies, possibly due to the sample size.…”
Section: Discussionmentioning
confidence: 79%
“…The "Imaging" study focused on the early phase of atherosclerosis, which is characterized by inflammation detected on PET imaging. PET has been used extensively to explore early atherosclerosis in heterozygous familial hypercholesterolemia (HeFH) 15 , diabetes mellitus 16 , and the general population. 17 PET scans provide insights into the pathophysiology of early plaque formation and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Any therapeutical intervention relying on GPR119 levels will benefit from PET imaging. Thus, our new strategy of PET imaging with [ 18 F]KSS3 may eventually provide real-time quantification 38 of GPR119 expression and distribution to enable biological, mechanistic, and therapeutic studies of T2DM. Our PET radioligand could be invaluable for GPR119 agonist drug development by establishing target engagement, dosing, metabolic stability, occupancy, and safety profiles.…”
Section: Parallel Artificial Membrane Permeability Assay (Pampa) For ...mentioning
confidence: 99%